Low back pain during pregnancy: prevalence, risk factors and clinical profile in the Bamenda Regional Hospital - Dobgima Walter Pisoh; Nzognou Tsopa Juny Karelle; Roland Ndouh Nchufor; Takang William Ako; Achuo Ascensius Ambe Mforteh; Merlin Boten; Theodore Tameh; Audrey-Fidelia Eyere Mbi-Kobenge; Moses Samje; Dohbit Julius Sama; Pascal Foumane (BMC Pregnancy and Childbirth)
Abstract Background Low back pain (LBP) is a significant musculoskeletal problem during pregnancy, which can negatively affect a woman’s quality of life. The aim of this study was to determine the prevalence, the clinical characteristics and the factors associated with LBP during pregnancy among women attending the Antenatal Unit of the Bamenda Regional Hospital (BRH). Methods A cross-sectional study was carried out from February to April 2019 at the Antenatal unit of the BRH. We included all pregnant women who came for antenatal consultation during the study period and who gave their informed consent to participate in the study. A pretested, interviewer-administered questionnaire was used to collect data on the sociodemographic characteristics of the participants, the occurrence of LBP, its clinical characteristics and the factors associated with its occurrence. Data were analysed using SPSS version 25.0. Univariate logistic regression was used to identify risk factors and multivariate analysis was used to eliminate confounders. A p-value of < 0.05 was considered statistically significant. Results A total of 410 participants were included in the study. The prevalence of LBP in pregnancy was 53.9% (n = 221). The prevalences of lumbar pain and pelvic girdle pain were 34.9% (n = 143) and 26.1%, (n = 107), respectively. The factors that were associated with a higher likelihood of reporting LBP were a history of LBP in a previous pregnancy (aOR = 2.9, 95% CI, p = < 0.001), obesity (aOR 3.4 95% CI, p = < 0.001), and using a soft mattress (aOR = 2.4 95% CI, p = 0.006). Exercise during pregnancy was found to be a protective factor (aOR = 0.2 95% CI, p = < 0.001). Conclusions Low back pain during pregnancy is a common problem among pregnant women attending antenatal care at the Bamenda Regional Hospital. Health workers need to be proactive in identifying LBP in pregnancy and managing it promptly.